2005
DOI: 10.1001/archpsyc.62.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Early-Stage Visual Processing and Cortical Amplification Deficits in Schizophrenia

Abstract: These findings confirm the existence of early-stage visual processing dysfunction in schizophrenia and provide the first evidence that such deficits are due to decreased nonlinear signal amplification, consistent with glutamatergic theories. Neuroimaging studies support the hypothesis of dysfunction within low-level visual pathways involving thalamocortical radiations. Deficits in early-stage visual processing significantly predict higher cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
305
2
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 345 publications
(351 citation statements)
references
References 81 publications
(118 reference statements)
38
305
2
6
Order By: Relevance
“…Deficits in M pathway processing, in particular, correlated significantly with global outcome. These deficits, which may be related to both structural and functional abnormalities within the early visual pathway in schizophrenia (Butler et al, 2005), are deserving of further study. A. Graph showing the group average waveforms for the high contrast (mixed M/P) condition over time for controls and patients with running t-test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deficits in M pathway processing, in particular, correlated significantly with global outcome. These deficits, which may be related to both structural and functional abnormalities within the early visual pathway in schizophrenia (Butler et al, 2005), are deserving of further study. A. Graph showing the group average waveforms for the high contrast (mixed M/P) condition over time for controls and patients with running t-test.…”
Section: Discussionmentioning
confidence: 99%
“…In the visual system, deficits have been shown to include increased visual thresholds (Cadenhead et al, 1997;Schechter et al, 2003), greater sensitivity to backward masking (Braff et al, 1991;Butler et al, 1996;Green and Nuechterlein, 1999a;Schechter et al, 2003), and decreased contrast sensitivity (Butler et al, 2005;Keri et al, 2002;Slaghuis and Curran, 1999), as well as motion perception (Chen et al, 1999;Li, 2002;Schwartz et al, 1999) and eye tracking deficits (Holzman et al, 1974;Levy et al, 1993;Trillenberg et al, 2004). Further, it has been suggested that these impairments may contribute to 'upstream' cognitive and social impairments (Brenner et al, 2002;Bruder et al, 1998;Kee et al, 1998;Ohno et al, 2000;Perry and Braff, 1994;Sergi and Green, 2003) and overall functional outcome of patients (Green et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with schizophrenia show deficits in early sensory information processing in the visual as well as the auditory modality (Butler et al, 2005;Javitt et al, 2000b). These impairments can be measured in behavioral paradigms (eg tone matching tasks, habituation, and prepulse inhibition of the startle response (PPI)), or EEG paradigms (mismatch negativity, P300, paired tone paradigm, peak recovery paradigm).…”
Section: Introductionmentioning
confidence: 99%